Understanding the Potential of Indonesian Museums - Qimyatussaadah Hafidz; Mala Sharma (Politeknik Negeri Madiun, 2022)
This study aims to provide ideas and explanations of the potential development and growth by understanding the strength and opportunities of museums in Indonesia. Descriptive research is deemed best acceptable for the purposes of this study. The data set include museum regulations in Indonesia, namely the Law of the Republic of Indonesia No. 5 of 2017 for Culture Promotion; Government Regulation of the Republic of Indonesia No. 66 concerning Museums; and museum statistical data. This research uses literature review as a data analysis approach by examining the documents that became research data, then assessing the potential for the development and growth of museums in Indonesia by identifying the opportunities and challenges. The results of the analysis are presented in the form of a narrative. The results show that regulations, the advancement of technology; as well as the Indonesian population, provide opportunities for museums in Indonesia to grow and develop in the future. However, the limited number of cultural heritage experts and the low interest of Indonesians in visiting historical sites make developing museums challenging.